The incorporation of body composition assessments as part of routine clinical care in a tertiary hospital's dietetic department: a best practice implementation project. Issue 1 (23rd March 2022) - Wilkinson, Shelley A.; Jobber, Chloe J.D.; Nave, Fiona; van der Meij, Barbara S.
ABSTRACT: Objectives: Our aim was to incorporate body composition assessment (BCA) into dietetic department procedures using interventions tailored to previously identified barriers and enablers. Introduction: BCA is recommended as part of routine malnutrition assessment and follow-up but is not yet part of usual care. Methods: Evidence-informed strategies to overcome barriers and enablers were operationalized and delivered as three overarching interventions: upskilling (professional development strategy), modelling and reducing fear of change (Clinical Champion project), and embedding as usual practice (departmental integration). Process evaluation assessed intervention fidelity. A survey assessed utilization of BCA devices, (perceived) competency, and attitudes of clinical dietitians towards BCA before and after interventions. Results: Two of the three elements were incorporated as planned (upskilling and embedding as usual practice), with one element (modelling and reducing fear of change) modified through iterative processes. The Clinical Champion project ran for 12 rather than 6 months, and resulted in the majority of champions confident with their skills, completing BCA within their daily clinical workload and feeling BCA was useful. Pre-surveys and post-surveys within the department of 26 dietitians showed a marked reduction in most perceived barriers and improved recognition of enablers across all theoretical framework domains; with a large proportion of 'not applicable' responses given for many barriers at follow-up. Conclusion: This evidence-informed implementation strategy successfully integrated BCA into dietitians' practice and departmental processes highlighting direction for future service changes. Continual assessment of barriers and success of integration into routine workloads is required to facilitate this.